2013
DOI: 10.1016/j.scr.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Generation of islet-like cells from mouse gall bladder by direct ex vivo reprogramming

Abstract: Cell replacement is an emerging therapy for type 1 diabetes. Pluripotent stem cells have received a lot of attention as a potential source of transplantable β-cells, but their ability to form teratomas poses significant risks. Here, we evaluated the potential of primary mouse gall bladder epithelial cells (GBCs) as targets for ex vivo genetic reprogramming to the β-cell fate. Conditions for robust expansion and genetic transduction of primary GBCs by adenoviral vectors were developed. Using a GFP reporter for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…We have recently shown that gall bladder derived epithelial cells can be reprogrammed to become endocrine-like and express insulin using a combination of Pdx1 , Ngn3 and MafA (Hickey et al, 2013). Others have shown that biliary duct cells in the liver can be reprogrammed in vivo and cure diabetes in mice (Akinci et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that gall bladder derived epithelial cells can be reprogrammed to become endocrine-like and express insulin using a combination of Pdx1 , Ngn3 and MafA (Hickey et al, 2013). Others have shown that biliary duct cells in the liver can be reprogrammed in vivo and cure diabetes in mice (Akinci et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These cells could also potentially be reprogrammed into hepatocytes and endocrine cells as demonstrated recently (4951). In addition, since laparoscopic cholecystectomy became clinically available in 1989, the removal of the gallbladder has become routine with 500,000 – 600,000 surgeries every year (52).…”
Section: Discussionmentioning
confidence: 91%
“…Aside from the close developmental ontogeny with the pancreas, the functional significance of PDX1 expression in adult human EHBCs is not fully known [9, 11]. It can be speculated that these cells may be more amenable to genetic reprogramming towards the pancreatic endocrine and could be a target for regenerative medicine in diabetes [20, 21]. …”
Section: Discussionmentioning
confidence: 99%